Estimated Effectiveness and Cost-effectiveness of a Fortified Edible Oils Program in Ethiopia. (29th May 2020) - Vosti, Stephen; Engle-Stone, Reina; Woldegebreal, Demewoz; Luo, Hanqi; Asfaw, Elias; Kagin, Justin; Moges, Tibebu; Tesfaye, Biniyam
Abstract: Objectives: In Ethiopia, standards for fortifying edible oil with vitamin A (VA) exist; they are not yet mandatory. This study assessed inadequate VA intake among children 6–35 months of age and women of reproductive age (WRA), modeled the potential impacts of VA-fortified edible oil on dietary VA adequacy and number of young lives saved, and estimated the cost-effectiveness of this program. Methods: Using an adapted 1-day version of the National Cancer Institute method, we analyzed national dietary intake data from the Ethiopian National Food Consumption Survey to estimate usual VA intake and calculate prevalence of inadequate intake (proportion below the Estimated Average Requirement). The Lives Saved Tool (LiST) was used to predict the number of lives saved among children. Program costs were estimated using an activity-based approach and applied to calculate cost-effectiveness of the oil fortification program. Results: Nationally, the prevalence of inadequate VA intake was high (∼80% children, ∼82% among women), with substantial spatial variation (children: 92% Amhara to 55% Gambella; WRA: 94% Amhara to 50% SNNP). Simulation results suggest that an edible oil fortification program (2000µg retinol/100g oil) would reduce, but not eliminate, inadequate VA intake among both groups. Nationally, a well-managed oil fortification program would reduce the prevalence of inadequate VA intake among children and WRA by ∼18 and ∼15 percentage points (pp), respectively; for children ∼38 pp in Addis Ababa but by only ∼8 pp in SNNP. Over 10 years, a well-managed program could save between ∼3700–5100 lives, just among non-breastfed children. A program to fortify imported oils (∼98% of all oils consumed in Ethiopia) with VA, including start-up investments and recurring M&E and border inspection activities, would cost ∼US$3.6m over 10 years. The cost-effectiveness of this program over a 10-year period would range from US$706-US$973 per life saved among non-breastfed children. Conclusions: Results suggest that fortifying imported edible oils in Ethiopia is a cost-effective way to save young lives. However, this program alone will not be sufficient to eliminate all VA deficiency. Many options for complementary programs exist; program- and region-specific cost-effectiveness measures can help guide policy discussions. Funding Sources: Bill & Melinda Gates Foundation.